2016
DOI: 10.18632/oncotarget.13344
|View full text |Cite
|
Sign up to set email alerts
|

miR-1 inhibits progression of high-risk papillomavirus-associated human cervical cancer by targeting G6PD

Abstract: Ectopic glucose-6-phosphate dehydrogenase (G6PD) expression may contribute to tumorigenesis in cervical cancer associated with high-risk human papillomavirus (HR-HPV 16 and 18) infections. Here, we demonstrate that microRNA-1 (miR-1) in association with AGO proteins targets G6PD in HR-HPV-infected human cervical cancer cells. miR-1 inhibited expression of a reporter construct containing a putative G6PD 3′-UTR seed region and suppressed endogenous G6PD expression. Down-regulation of miR-1 increased G6PD express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…Abnormal expression of miRNAs has been involved in the initiation and progression of human cancer (10,11). The tumor suppressive function of miR-1 in cancer has been revealed in recent years (39,(43)(44)(45). Downregulation of miR-1 was shown to enhance the tumorigenesis and invasiveness of oral squamous cell carcinoma (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal expression of miRNAs has been involved in the initiation and progression of human cancer (10,11). The tumor suppressive function of miR-1 in cancer has been revealed in recent years (39,(43)(44)(45). Downregulation of miR-1 was shown to enhance the tumorigenesis and invasiveness of oral squamous cell carcinoma (46).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the activity of G6PD resulted in tumor suppressive functions. The negative regulation of G6PD by miRNAs has been demonstrated in recent studies (38,39); G6PD was modulated by miR-206 and shown to be critical for the differentiation of rhabdomyosarcoma (38). Additionally, it has been reported that miR-1 post-transcriptionally repressed the expression of G6PD, increased the ROS level and aggravated the cardiac oxidative stress (40).…”
Section: Introductionmentioning
confidence: 88%
“…The potential target sites for miR-449a on the mouse ScN2B mRNA 3'-UTR seed regions, including both wild-type (wt) and mutant (mut) sequences, were cloned. The artificially cloned sequences were inserted downstream of the luciferase reporter gene, pGL3 (Guangzhou RiboBio co., Ltd.), to generate the ScN2B 3'-UTR-wt and ScN2B 3'-UTR-mut vectors, as described previously (40,41). Briefly, 293T cells (purchased from Institute of Biochemistry and cell Biology, Shanghai, china) were seeded in 96-well plates and co-transfected with 100 ng/ml of each pGL3-ScN2B 3'-UTR-wt or -mut vector and 35 nM miR-449a mimics or Nc (Guangzhou RiboBio co., Ltd.).…”
Section: Rna Immunoprecipitation Chip (Rip-chip)mentioning
confidence: 99%
“…Mice were randomly assigned to each of the following 9 groups (n=5): normal BEAS-2Btreated group; miR-768-3p overexpression human NSCLC cell (A549/HCC4006-miR-768-3p-mimics)-treated groups; miR-768-3p functional deficient NSCLC cell (A549/HCC4006-miR-768-3p-antagomir)-treated groups; matched control groups (A549/HCC4006-mimics-NC and A549/HCC4006antagomir-NC). As described before, cells were harvested, digested and injected intradermally into the left axilla of the nude mice(20,21). After seeding, liquid absorption at the injection site, tumor growth (volume and weight), and mouse survival were measured.…”
mentioning
confidence: 99%